Foreign Direct Investment and its Impact on Value Added in the Industrial Sector of the Kingdom of Saudi Arabia - Nasrulddin, Vivian Mohammed Saleh; Khayat, Sahar Hassan; Alharbi, Maha Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of foreign direct investment on the added value of the industrial sector in the Kingdom of Saudi Arabia during the period (2000-2020). A multiple linear regression analysis model has been described, to express the relationship between the added value of the industrial sector as a percentage of GDP -as a dependent variable-, and the independent variables associated with foreign direct investment, which were selected based on previous studies and the researcher’s diligence, which are represented in: the foreign direct investment index, the possibility of attracting investments, the economic stability index, and the economic risk index. By identifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified, by the statistical program E-views. As expected, the results showed a direct relationship between the dependent variable and both: the flow of foreign investments, growth in per capita GDP, and industrial exports, in addition to an inverse relationship between the dependent variable and the inflation rate. Contrary to what was expected, the results showed an inverse relationship with national spending from GDP.